Facies Distribution and Petrophysical Properties of Shoreface-Offshore Transition Environment in Sandakan Formation, NE Sabah Basin - Majid, M.F.A. (Institute of Physics Publishing, 2017)
Newly exposed outcrop of Miocene shallow marine sandstone in Sandakan Formation, allows characterization of the facies distribution and petrophysical properties of shoreface to offshore transition environment. Six facies are defined: (1) Poorly bioturbated Hummocky Cross Stratified (HCS) sandstone (F1), (2) Moderately bioturbated HCS sandstone (F2), (3) Well bioturbated HCS sandstone (F3), (4) Poorly bioturbated Swaley Cross Stratified (SCS) sandstone (F4), (5) Interbedded HCS sandstone with sand-silt mudstone, (6) Heterolithic mudstone. The sedimentary successions were deposited in upper to lower shoreface, and offshore transition environment. Facies F3, F4 and F5 shows good reservoir quality with good porosity and fair permeability values from 20 to 21 and 14 mD to 33 mD respectively. While Facies F1 exhibits poor reservoir quality with low permeability values 3.13 mD. © Published under licence by IOP Publishing Ltd.